2013
DOI: 10.1073/pnas.1220015110
|View full text |Cite|
|
Sign up to set email alerts
|

Receptor-like kinase SOBIR1/EVR interacts with receptor-like proteins in plant immunity against fungal infection

Abstract: The plant immune system is activated by microbial patterns that are detected as nonself molecules. Such patterns are recognized by immune receptors that are cytoplasmic or localized at the plasma membrane. Cell surface receptors are represented by receptor-like kinases (RLKs) that frequently contain extracellular leucine-rich repeats and an intracellular kinase domain for activation of downstream signaling, as well as receptor-like proteins (RLPs) that lack this signaling domain. It is therefore hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
486
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(500 citation statements)
references
References 53 publications
12
486
0
2
Order By: Relevance
“…The RLK SOBIR1 was initially identified as a suppressor of BIR1 that regulates cell death (Gao et al, 2009). More recent studies show that tomato SOBIR1 particularly interacts with LRR-RLPs that play a role in defense against fungal pathogens (Liebrand et al, 2013). Experiments presented here show that Arabidopsis SOBIR1 interacts with RBPG1 and is essential for RBPG1-mediated responsiveness to PGs.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The RLK SOBIR1 was initially identified as a suppressor of BIR1 that regulates cell death (Gao et al, 2009). More recent studies show that tomato SOBIR1 particularly interacts with LRR-RLPs that play a role in defense against fungal pathogens (Liebrand et al, 2013). Experiments presented here show that Arabidopsis SOBIR1 interacts with RBPG1 and is essential for RBPG1-mediated responsiveness to PGs.…”
Section: Discussionmentioning
confidence: 66%
“…The current paradigm for signaling via RLPs is heterodimerization with RLKs (Bleckmann et al, 2010;Liebrand et al, 2013). The RLK SOBIR1 was initially identified as a suppressor of BIR1 that regulates cell death (Gao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that SOBIR1 physically interacted with Cf-4, Ve1, LepR3, Rlm2, AtRLP1, AtRLP23, AtRLP30 and AtRLP42, and was required for the proper function of these RLPs. 9,10,12,13,15,16,[24][25][26] However, it is unclear about the biological relevance of the physical interaction between SOBIR1 and two developmental RLPs CLV2 and TMM, respectively. It could postulate that SOBIR1 may involve in the CLV2-and/or TMM-mediated developmental processes.…”
Section: Introductionmentioning
confidence: 99%